2020
DOI: 10.1016/j.cognition.2020.104190
|View full text |Cite
|
Sign up to set email alerts
|

Statistical regularities shape semantic organization throughout development

Abstract: Our knowledge about the world is represented not merely as a collection of concepts, but as an organized lexico-semantic network in which concepts can be linked by relations, such as "taxonomic" relations between members of the same stable category (e.g., cat and sheep), or association between entities that occur together or in the same context (e.g., sock and foot). To date, accounts of the origins of semantic organization have largely overlooked how sensitivity to statistical regularities ubiquitous in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 64 publications
(111 reference statements)
0
25
0
Order By: Relevance
“…Wulff et al [1] proposed learning as another component that is vital for the mental lexicon. As laid out in the Introduction, statistical learning is of importance for the development of the semantic network (see: [16]). A less developed semantic lexicon for adolescents with ID could be explained by reduced statistical learning ability.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Wulff et al [1] proposed learning as another component that is vital for the mental lexicon. As laid out in the Introduction, statistical learning is of importance for the development of the semantic network (see: [16]). A less developed semantic lexicon for adolescents with ID could be explained by reduced statistical learning ability.…”
Section: Discussionmentioning
confidence: 99%
“…See Figure 1 for visual representation of the three measures. It has been argued that the structure of the semantic network might be the result of statistical learning, a process where taxonomic categories are formed based on co-occurrence regularities [16]. Evidence suggests that statistical learning is apparent in children as young as 4-5 years of age [16].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Statistical learning has been suggested to be an important cognitive skill for this (Erickson & Thiessen, 2015;Kidd et al, 2018). Unger (2020) found that statistic regularities in the language input are used to group words into categories. Words that occur within the same context are likely to belong to the same category.…”
mentioning
confidence: 99%